Meaning and Interpretation : Wittgenstein, Henry James, and Literary Knowledge - Hagberg, Garry, 1952- (Book collections on Project MUSE., 1994)
This book examined Wittgenstein's account of the importance of particularized usage and of context in determining the meaning of word or work of art. Adopting a Wittgensteinian method in close readings of the short fiction of Henry James, the author revealed how literary interpretation itself may be practiced as a form of philosophical investigation.